2021
DOI: 10.1021/acsaem.1c02277
|View full text |Cite
|
Sign up to set email alerts
|

Fullerene-Free All-Small-Molecule Ternary Organic Solar Cells with Two Compatible Fullerene-Free Acceptors and a Coumarin Donor Enabling a Power Conversion Efficiency of 14.5%

Abstract: Organic solar cells (OSCs) based on a ternary single bulkheterojunction using either donor:donor:acceptor or donor:acceptor:acceptor with complementary absorption profiles and well-matched energy levels can effectively improve the power conversion efficiency (PCE). Herein, we report the fabrication of binary and ternary OSCs using a wide-band-gap donor molecule C2 in combination with two fullerene-free acceptors (FFAs), i.e., a medium-band-gap DBTBT-IC and a low-band-gap AQx-3. After incorporation of DBTBT-IC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Additionally, the fill factor (FF) of the PSCs is improved, and the charge carrier transit is improved by an appropriate cascade energy level structure, which also suppresses the recombination processes . In some cases, the third component can act as an additional energy donor by forming an efficient energy transfer channel with the host binary system and improving the efficiency of photogenerated exciton generation. This occurs when the third component’s PL spectrum overlaps with the host’s (donor or acceptor) absorption spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the fill factor (FF) of the PSCs is improved, and the charge carrier transit is improved by an appropriate cascade energy level structure, which also suppresses the recombination processes . In some cases, the third component can act as an additional energy donor by forming an efficient energy transfer channel with the host binary system and improving the efficiency of photogenerated exciton generation. This occurs when the third component’s PL spectrum overlaps with the host’s (donor or acceptor) absorption spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Sharma and co-workers reported a PCE of 13.1% with a Δ E HOMO of 0.14 eV . Our group recently reported two coumarin-based wide band gap donor molecules (C1 and C2) attaining PCEs of 11.1–14.5% in ternary OSCs with low E loss . The blend of C2:BThIND-Cl and C2:Y6 acceptors showed PCEs of 9.46% and 9.72%, respectively, despite a small Δ E HOMO of 0.02–0.04 eV resulting from the reduction of the nonradiative loss …”
Section: Introductionmentioning
confidence: 99%
“…Hence, the inclusion of the third component into the binary blend offers a simplistic approach to improve the light harvesting properties as well as stability. [21][22][23][24][25][26][27] Zhu and co-workers recently reported a PCE of 18% using a polymer donor PM6 along with Y6 and AQx-3 as dual-electron acceptors. [28] The "two-in-one" strategy reinforced the film morphology via alloy formation facilitating charge generation and transport.…”
mentioning
confidence: 99%
“…Recent literatures revealed that the use of coumarin-based donor molecules [25,27,29] in the photoactive layer can compete with the well-known donor molecules based on benzodithiophene (BDT), diketopyrrolopyrrole (DPP), oligothiophenes, and dithienopyrrole (DTP). [30][31][32][33][34][35] The coumarin derivatives possess well-matched energy levels, light absorption in the high-energy region of the visible spectrum, and suitable miscibility properties with the fullerene-free acceptors, offering PCE up to 15% in ternary OSCs.…”
mentioning
confidence: 99%